α-Methylacyl-CoA Racemase from Mycobacterium tuberculosis—Detailed Kinetic and Structural Characterization of the Active Site - Otsile O. Mojanaga; Timothy J. Woodman; Matthew D. Lloyd; K. Ravi Acharya (Biomolecules, 2024)
α-Methylacyl-CoA racemase in M. tuberculosis (MCR) has an essential role in fatty acid metabolism and cholesterol utilization, contributing to the bacterium’s survival and persistence. Understanding the enzymatic activity and structural features of MCR provides insights into its physiological and pathological significance and potential as a therapeutic target. Here, we report high-resolution crystal structures for wild-type MCR in a new crystal form (at 1.65 Å resolution) and for three active-site mutants, H126A, D156A and E241A, at 2.45, 1.64 and 1.85 Å resolutions, respectively. Our analysis of the new wild-type structure revealed a similar dimeric arrangement of MCR molecules to that previously reported and details of the catalytic site. The determination of the structures of these H126A, D156A and E241A mutants, along with their detailed kinetic analysis, has now allowed for a rigorous assessment of their catalytic properties. No significant change outside the enzymatic active site was observed in the three mutants, establishing that the diminution of catalytic activity is mainly attributable to disruption of the catalytic apparatus involving key hydrogen bonding and water-mediated interactions. The wild-type structure, together with detailed mutational and biochemical data, provide a basis for understanding the catalytic properties of this enzyme, which is important for the design of future anti-tuberculosis drug molecules.